Representation of the natural world in Marseilles Pan'gol's “Souvenirs d'enfance” (Literatures of the World: Poetics, Mentality and Spirituality, 2017)
The article is devoted to the study of the natural world in the autobiography of childhood «Souvenirs d’enfance» by Marcel Pagnol, member of the French Academy, famous French playwright, theatre and film Director, writer, poet, essayist of the twentieth century. It traced that nature in the memoirs of Marcel Pagnol are classic archetypes of the mother deity, a mother, a wise mentor. The nature gives strength, teaches wisdom, reveals the inner reserves of the person. The nature for the main character of memories is primarily freedom, harmony with oneself and the environment. The attention is focused on the fact that in «Souvenirs d'enfance» nature presents its main constituent elements – water, earth, flora and fauna, the atmosphere. For their description widely used acoustic and visual features, is fed through a cinematic writing technique. In the memoirs literary work of Marcel Pagnol the nature appears as a holistic system, which for centuries lives by its own laws, in your usual and slow tempo. Moving away from nature, man speeds up the tempo of his life, however, in the opinion of the writer, completely break away from it cannot, because it is part of nature, their bond is strong and lasts throughout human life.
Keywords: childhood; memories; nature; concept NATURE; the mother archetype-deity; the archetype of mother; the archetype of the wise mentor